Model Pembelajaran Discovery Dengan Pendekatan Konflik Kognitif Berorientasi Pada Kemampuan Berpikir Kritis Peserta Didik - P. Ayu Suci Lestari; Gunawan Gunawan; Kosim Kosim (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2019)
This study aims to develop an instructional materials by discovery model with a cognitive conflict approach that has a positive impact on students' critical thinking skills, especially on temperature and heat material. The development of this instructional materials adapted the 4D (define, design, develop, and disseminate). Instructional materials developed in the form of syllabus, lesson plans, student worksheet, learning materials, as well as instruments of critical thinking skills in the form of a essay questions. This product was validated by three expert validators and obtained very high validity criteria. The practicality test is done by observing the implementation of learning accompanied by the questionnaire responses of teachers and students, and produces very high practicality criteria. The final value of critical thinking skills students also have high criteria. Therefore, the product developed can be declared valid, practical, and has a positive impact on students' critical thinking skills.